Maternal and fetal outcomes in women with cerebrovascular malformations in pregnancy: A multicentre retrospective cohort study. (22nd December 2021) - Cauldwell, Matthew; Bredaki, Emma; Dassan, Pooja; Dhanjal, Mandish K.; Kaler, Mandeep; Madipola, Nissanka; Mahmud, Mohammad; Paviour, Dominic; Senvar, Naz; de Silva, Rajith; Watt‐Coote, Ingrid; Williams, David; et al.
Abstract: Objective: To determine maternal, obstetric and neonatal outcomes in a cohort of women with cerebrovascular malformations (CVMs) that include arterial venous malformations (AVMs) and cavernomas. Design: Retrospective cohort study. Setting: Six specialist centres managing pregnant women with neurological disorders. Population: Sixty‐three women with CVMs in 83 pregnancies of ≥20 completed weeks' gestation. Methods: Retrospective case notes review. Main outcome measures: Neurological outcomes including rates of acute cerebral bleeding in pregnancy and reported seizures during pregnancy. Maternal outcomes included number of women with a livebirth and the proportion of women being delivered by caesarean section. Results: Most women had a good pregnancy outcome with high rates of vaginal delivery (73%) at term. There were no maternal deaths. Six women had an acute cerebral bleed, all of whom were delivered by planned caesarean section. In total, ten women had seizures in pregnancy (of whom four also had a bleed). Six (7%) babies were admitted to a neonatal unit. There was no significant difference in outcomes between women with AVMs and those with cavernomas. Conclusion: In the majority of cases, pregnancy outcomes were favourable, with most women having a vaginal delivery. All cases of cerebral bleeds that occurred were at a remove from the peripartum period. Tweetable Abstract: Women with cerebrovascular malformations have high rates of vaginal delivery. Tweetable Abstract: Women with cerebrovascular malformations have high rates of vaginal delivery.